The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.erss.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Community acceptance of large-scale solar energy installations in developing countries: Evidence from Morocco

Abstract: Renewable energy production is climbing the public agenda in many countries in the Middle East and North Africa (MENA region), for reasons of energy security, independence and local value creation. While technical and economic barriers are largely understood, in this paper we investigate the issue of community acceptance. In so doing, we explore the importance of relevant drivers of community acceptance such as level of expected socioeconomic and environmental impacts, procedural and distributive justice, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(42 citation statements)
references
References 40 publications
0
34
1
2
Order By: Relevance
“…Another study was deployed in the Malaysian context, about views and perceptions of the local population towards solar energy and the installation of photovoltaics; it was concluded that the Malaysians hardly understood the incentives and the wider socio-economic benefits derived, thus they were reluctant to invest in photovoltaics [33]. Additionally, in the Middle East and North Africa, the attribute of social opposition was reported among interviewed citizens, since they expressed a biased behavior, significantly distorting anything that tends to become socially acceptable [34]. On the other hand, a study about the social acceptance of small hydropower plants (SHP) in India revealed that SHP projects are regionally challenging forms that can be directly utilized in the Indian energy mix of production [35].…”
Section: Introductionmentioning
confidence: 99%
“…Another study was deployed in the Malaysian context, about views and perceptions of the local population towards solar energy and the installation of photovoltaics; it was concluded that the Malaysians hardly understood the incentives and the wider socio-economic benefits derived, thus they were reluctant to invest in photovoltaics [33]. Additionally, in the Middle East and North Africa, the attribute of social opposition was reported among interviewed citizens, since they expressed a biased behavior, significantly distorting anything that tends to become socially acceptable [34]. On the other hand, a study about the social acceptance of small hydropower plants (SHP) in India revealed that SHP projects are regionally challenging forms that can be directly utilized in the Indian energy mix of production [35].…”
Section: Introductionmentioning
confidence: 99%
“…(3) Eco-friendliness-the degree to which the energy source claims to reduce, minimize, or do no harm to the environment-is also a significant determinant of energy acceptance. A greater perception of eco-friendliness generally leads an individual to perceive the energy source as low in environmental risk and thus renders the source more acceptable [20,[35][36][37][38]. 4The contribution to the country's economic development is an economic benefit that an energy source provides at the macro-level.…”
Section: Sample and Data Collectionmentioning
confidence: 99%
“…They are the general criteria that determine the optimum size of the photovoltaic system: technical, economic, environmental, and social criteria. Fourteen sub-criteria are selected from almost 70 determining factors that affect the optimal size of a distributed generation photovoltaic system (Table 2) that recent studies have shown [43][44][45][46][47], according to the criterion to which they belonged. These sub-criteria were divided into quantitative and qualitative according to the characteristics of measurement in each case.…”
Section: Criteria and Factors To Consider For The Optimal Size In Pvmentioning
confidence: 99%